Member States in the EU: The Issue of (Pooled) Sovereignty - Petr, Michal (Federalism as the Future of the Diverse EU?, 2025)
It has been argued by some scholars that within the European Union, Member States are no longer sovereign. Others claim that the sovereignty of Member States is not lost, but “pooled” with the sovereignty of other members. Still others argue that the notion of sovereignty has itself has changed and it needs to be understood in a modern (or even postmodern) way. This paper analyses the notion of sovereignty, both generally and specifically in the EU context. I argue that, in practical terms, Member States remain sovereign within the EU, meaning that no decision can be taken without their consent as they wield the veto power. The relationship between the EU and its Member States thus remains horizontal in principle, without a simple hierarchy. However, this approach is challenged by the existence of qualified majority voting, which allows one Member State to be “overvoted” by others. Admittedly, this may be the price of efficient decision-making, but it dramatically changes the position of a Member State within the EU. In this context, I put forward that two conditions must be met for a Member State to retain sovereignty in such circumstances. First, the competences of the EU and the Member States need to be clearly delimitated. In particular, the Member States need to be absolutely free to decide which decisions should be subject to unanimity and qualified majority voting. And second, the power to decide whether certain competences remain with the Member State or have been transformed to the EU must remain with the Member State concerned. The number of recent ultra vires judgments of national constitutional courts shows that the Member State understand this in the same way. Keywords: competences; constitutionalism; qualified majority voting; sovereignty; ultra vires.